Pattern of Paediatric Mortality of hospitalized patients in a Tertiary Care Hospital Rawalpindi - RaiMuhammadAsghar,MuddassarSharif,KhalidSaheel,RaiRijjalAshraf,AbidHussain, RaiMuhammadAsghar,MuddassarSharif,KhalidSaheel,RaiRijjalAshraf,AbidHussain (Journal of Rawalpindi Medical College, 2020)
Introduction: Mortality of children is the prime indicator of a country’s health status and its development. Understanding child mortality among different age groups is one of the valuable public health insights. Therefore, studies regarding child mortality patterns are essential for re-evaluating existing health services. Objective: The objective of this study is to describe the pattern of paediatric mortality in our hospital. Materials and Methods: A retrospective analysis was done with the medical records of Pediatric patients (up to 12 years)who died in the Pediatrics department of Benazir Bhutto Hospital, Rawalpindi from 1stJan2018 to 31stDec 2018. Results: A total of 15,500 children were admitted to the Paediatric department from 1st January 2018 to 31st December 2018. A total of 1738 deaths were recorded. The overall mortality of 11.3% was noted in the cases admitted to the Paediatric Department. Conclusion: Septicemia, Acute respiratory infection(ARI)/Pneumonia, Birth asphyxia, and low birth weight (LBW)/prematurity were the major causes of pediatrics mortality.